SOCIAL POLICY: THEORY, METHODOLOGY AND PRACTICAL ASPECTS OF TEACHING AND IMPLEMENTATION IN THE PROFESSIONAL ACTIVITY OF SOCIAL WORKERS - SOLNYSHKINA , Alina (Social work and education, 2024)
The scientific article represented an analysis of theoretical and methodological approaches to the study and teaching of social policy. The concept of "Social policy" is defined as a synthesis of theoretical and methodological approaches, as an educational discipline for students - future social workers, and as a practical activity aimed at reducing social tension in society and a tool of social justice. The author of the article analyzes the key problems of studying the problems of social policy and methods of teaching the discipline "Social Policy" in the period of a full-scale invasion. The main accents of the scientific publication are the principles, values, and effective tools of the state’s social policy. Innovative teaching methods can help students - future social workers to understand the main problems of socio-economic inequality, gender aspects of social policy, methods, and directions of social protection of vulnerable categories of the population. Discussion of the results of sociological research, publications, and development of own projects made a great contribution to the development of critical thinking. The connection of the main directions and methods of social policy with the functioning and development of leading social institutions will help the practical implementation of knowledge in the everyday reality of social workers. Examples of discussions and realization of practical cases during the teaching of Social Policy as an educational discipline are offered for the analysis of social initiatives and programs in the context of various models of social policy. The active using of practical experience in the implementation of social programs and initiatives is proposed in the scientific article